Sex differences in DNMT3A-mutant clonal hematopoiesis and the effects of estrogen - Julia Stomper; Abhishek Niroula; Roger Belizaire; Marie McConkey; Tagore Sanketh Bandaru; Benjamin L. Ebert (Cell Reports)
Summary: Blood cancers are generally more common in males, and the prevalence of most mutations that drive clonal hematopoiesis and myeloid malignancies is higher in males. In contrast, hematopoietic DNMT3A mutations are more common in females. Among ∼450,000 participants in the UK Biobank, the prevalence of DNMT3A mutations and copy-number abnormalities is higher in females than males. In a murine model, Dnmt3a-mutant hematopoietic stem cells (HSCs) from unperturbed female mice had increased stemness gene expression compared to male and wild-type (WT) mice. Estrogen regulates HSCs, and we found that Dnmt3a mutations maintain stemness in the setting of estrogen-induced proliferative stress. Dnmt3a-mutant myeloid cells outcompeted WT cells under chronic estrogen treatment, an effect that was dependent on cell-intrinsic estrogen receptor alpha activity. Our studies indicate that estrogen might contribute to the female predominance of DNMT3A-mutant clonal hematopoiesis.